Peningkatan Ekspresi GSH (Gluthathione) pada Monosit yang Dipapar Biji Kopi dan DMBA (7,12-dimethylbenz(a)anthrancene) - I Dewa Ayu Ratna Dewanti (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2016)
Background. The content of the coffee beans that are antioxidants have good potential, particularly against cancers of the oral cavity. Polyphenols in coffee beans 5% together the other ingredients in the diet, such as vitamin C, vitamin E and carotenoids, can protect the body's tissues against oxidative stress. Antioxidants can prevent a variety of diseases associated with oxidative stress, such as cancer. Objective. Research to determine the expression of GSH on monocytes were exposed to coffee beans and DMBA in vitro. Research Methods. Monocytes aspirated, added RPMI, resuspension with M 199, penstrep, fungisone. Superimposed on a cell culture plate that was given coverslip, added M 199, incubation. Add RPMI, incubation, discard lymphocytes, washing with RPMI. Add medium M 199, incubation. Cultures are washed, resuspension with M 199, treatments according to the research group. KO: Monocytes, K1: Coffee Monocytes + 10% + DMBA, K2: Coffee Monocytes + 5% + DMBA, K3: Monocytes + Coffee 10%, K4: Monocytes + coffee 5%, K5: Monocytes + DMBA. Immunocytochemistry for the analysis of GSH. Cells expressing GSH brown under a light microscope with a magnification of 400 times and counted on five visual fields. Research Result. Results of ANOVA analysis (p <0.01) showed that there were significant differences in all groups. Furthermore, the LSD test (p <0.05), the results are significant differences between all groups. Conclusion. Coffee beans can increase GSH expression on monocytes were exposed to DMBA.